Software Tools Used for Continuous Assessment - Corina SBUGHEA; Maria Cristina ENACHE (Analele Universității "Dunărea de Jos" Galați. Fascicula I, Economie și informatica aplicata, 2016)
he present paper addresses the subject of continuous evaluation and of the IT tools that support it. The approach starts from the main concepts and methods used in the teaching process, according to the assessment methodology and, then, it focuses on their implementation in the Wondershare QuizCreator software.